Synergistic magneto-aeration photocatalysis over AgI/TiO2/mrGO composite for high-salinity recalcitrant wastewater - Chunxia Zhao; Bingqian Wei; Feng Lin; Hongyang Xue; Yuxin Li; Miaomiao Cheng; Hongjie Wang (Chemical Engineering Journal, 2026)

Illicium verum polysaccharide targets fimbriae and flagella to disrupt biofilm and inhibit multidrug-resistant Escherichia coli proliferation - Yifei Xiang; Erqiang Wang; Xuelian Mo; Zhifei Wei; Zhiran Xu; Wenjing Li; Changhua Lin; Yanwen Zhang; Chunxia Ma; Bin Zheng; Ziyang Li; Chengzhi Liu; et al. (Carbohydrate Polymers, 2026)

Riverbank line migration dynamics and channel evolution processes along the Tarim River in China - Yun Zhao; Lin Li; Quanli Zong; Kai Jin; Chunxia Liu; Peng Qin; Xiuzhi Zhu (Journal of Arid Environments, 2026)

Experimental investigation on liquefaction resistance of saturated silty soil: effects of clay content and intergranular void ratio - Chunxia Huang; Lin Wang; Yanshun Chen; Liang Zhang; Lei Wang; Dong-Sheng Jeng (Bulletin of Engineering Geology and the Environment, 2026)

Unveiling polycyclic aromatic hydrocarbons exposure and female infertility risk in southern China: An integrated epidemiologic and network toxicology approach - Chuhang Lin; Qian Chen; Qianqian Xie; Haiying Li; Xiaomei Wu; Xiaoxiao Lin; Lijun Wang; Xingming Zhong; Lei Tan; Chunxia Jing (Reproductive Toxicology, 2026)

Salvianolic Acid B Inhibits Ferroptosis Through ACSL4 Pathway Regulation in sepsis-associated encephalopathy Mice - Xingyao Li; Zhizhun Mo; Yumei Yang; Chunxia Zhao; Shuwen Zhang; Yan Lin; Yuxiang Liu; Ling Wang; Xiaolong Xu; Qingquan Liu; Kai Fan (Molecular Neurobiology, 2026)

Paeoniflorin attenuates hyperprolactinemia by targeting the pituitary mPRα-mediated, dopamine receptor-independent signaling in vivo and in vitro - Bingqi Lin; Yun Yi; Xiaolan Mo; Yifan Yang; Yuhao Li; Chunxia Wang; Yuanyi Wei (Toxicology and Applied Pharmacology, 2025)

Elucidation of Pt-Co synergistic effects in Pt30-Co50@WNxC1−x/W electrodes via operando DRT for enhanced HER kinetics - Yinquan Zhang; Hui Song; Tianjiao Lou; Wenqing Liu; Chunxia Lin; Jiangwen Xu; Guangshun Ran; Jinxu Song; Yukun Chang; Hongyi Li; Jinshu Wang (Chemical Engineering Journal, 2025)

Biological age acceleration mediates effects of household air pollution from solid fuels on dementia risk: A prospective cohort study in China - Haisheng Wu; Zengxian Lin; Chunren Zhang; Yuxing Jiang; Liming Bai; Jiazhen Zheng; Suosu Wei; Chunxia Deng (Environmental Pollution, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Green biotechnological synthesis of rare sugars/alcohols: D-allulose, allitol, D-tagatose, L-xylulose, L-ribose - Xin Wen; Mesfin Angaw Tesfay; Yuhang Ning; Huibin Lin; Guangwen Liu; Hongtao Hu; Xixian Xu; Xingbo Jiang; Chunxia Zhao; Yilin Ren; Can Li; Chengjia Zhang; et al. (Food Research International, 2025)

Study of the Drug Resistance Function of Ivermectin-Resistance-Related miRNAs in Haemonchus contortus - HaiFeng Wen; YanMin Zhang; Lin Yang; WenLong Wang; ChunXia Liu (Acta Parasitologica, 2025)

Preparation of the sandwiched PS-SiO2-PVAc-SiO2 electrospinning fiber membrane with super-hydrophobic and self-cleaning and its performance in oil-water emulsion separation - Yang Hu; Xiaoyan Lin; Datong Liu; Lili Liang; Chunxia Pang; Xunhai Pan (Journal of Environmental Chemical Engineering, 2024)

Oxidative stress mediates the association of organophosphate flame retardants with metabolic obesity in U.S. adults: A combined epidemiologic and bioinformatic study - Chuhang Lin; Ziang Guo; Haiying Li; Zhengtian Lai; Jing Zhang; Shen Xie; Yuxuan Tan; Chunxia Jing (Environmental Pollution, 2024)

Constructed wetland coupled microbial fuel cell (CW-MFC) with Phragmites australis planted for hexavalent chromium removal and electricity generation - Chunxia Mu; Kelei Huang; Lin Wang (Journal of Water Process Engineering, 2024)

Wind erosion prevention and trans-boundary ecosystem service payments in the Hunshandake region - Mengdong Huang; Yu Xiao; Changshun Zhang; Lin Zhen; Keyu Qin; Jingya Liu; Jie Xu; Shuang Gan; Jia Liu; Chunxia Lu; Gaodi Xie (Journal of Cleaner Production, 2024)

Distinct species turnover patterns shaped the richness of antibiotic resistance genes on eight different microplastic polymers - Weihong Zhang; Jun Geng; Mengge Sun; Chunxia Jiang; Hui Lin; Haiyang Chen; Yuyi Yang (Environmental Research, 2024)

Optimizing carbonation reaction parameters of calcium carbide slag in acidic/alkaline environment enhancing CO2 mineralization efficiency - Zihe Pan; Lin Chen; Chunxia Cao; Fengjie Zhang; Huirong Zhang; Yanxia Guo (Chemical Engineering Journal, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Retraction Note: Coordination evaluation of urban tourism and urban development based on TOPSIS method—a case of Xiamen city - Chunxia Zheng; Yawei Wu; Yanqing Lin; Yawen Zheng (Environmental Science and Pollution Research, 2024)

Experimental study on liquefaction influence factors of saturated silty soil using orthogonal design method - Chunxia Huang; Tong Cao; Lin Wang; Liang Zhang; Yanshun Chen; Lei Wang (Bulletin of Engineering Geology and the Environment, 2024)

Antioxidant peptide ETT from Isochrysis zhanjiangensis attenuate skin aging by maintaining homeostasis and promoting collagen generation - Yuan-Lin He; Yi Liu; Liyuan Lin; Yinhuan Mo; Huijuan Li; Chunxia Zhou; Pengzhi Hong; Zhong-Ji Qian (Algal Research, 2024)

The effects of impurities in carbide slag on the morphological evolution of CaCO3 during carbonation - Zihe Pan; Chunxia Cao; Bo Wang; Fengjie Zhang; Lin Chen; Jianjun Zhao; Zhien Zhang; Huaigang Cheng (Journal of Environmental Management, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Association between polycyclic aromatic hydrocarbons and infertility in U.S. women: National Health and Nutrition Examination Survey 2013–2016 - Xiaomei Wu; Suixiang Wang; Xiaoxiao Lin; Huanzhu Liang; Yingying Wu; Yuxuan Tan; Huixian Zeng; Qian Chen; Jie Wang; Feng Huang; Ziang Guo; Puyi Xing; et al. (Reproductive Toxicology, 2024)

Chemically tailored molecular surface modification of bamboo pulp fibers for manipulating the electret performance of electret filter media - Chunxia Pang; Huanhuan You; Sijie Lei; Fan Su; Lili Liang; Zhanguo Li; Xiaoyan Lin; Yaping Zhang; Hao Zhang; Xunhai Pan; Yang Hu (Carbohydrate Polymers, 2024)

Asynchronous variations of mercury accumulation since the last deglaciation in the eastern and western Nanling mountains in South China - Xiaojun Wang; Wei Zhong; Mingying Quan; Tianhang Li; Durui Lin; Chunxia Zhang (Quaternary Science Reviews, 2024)

Detection of acrylamide in food based on MIL-glucose oxidase cascade colorimetric aptasensor - Kaixi Guo; Xianfeng Lin; Nuo Duan; Chunxia Lu; Zhouping Wang; Shijia Wu (Analytica Chimica Acta, 2024)

Exosomal miRNA analysis provides new insights into exposure to nanoplastics and okadaic acid - Linhong Yan; Peichun Lin; Zijie Wu; Zifan Lu; Lihua Ma; Xiaoling Dong; Lei He; Zhenqing Dai; Chunxia Zhou; Pengzhi Hong; Chengyong Li (Science of The Total Environment, 2023)

Shallow subsurface habitats across the Mars-analog Qaidam Basin - Yan Chen; Li Liu; Huiqing Zhang; Xue Guo; Wensi Zhang; Chunxia Zhang; Wei Lin (Science China Earth Sciences, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Structural Characterization and Biological Activity of Oligopeptides from Isochrysis zhanjiangensis: Based on Quantum Mechanics, Molecular Docking and in Vitro Experiments - Liyuan Lin; Huijuan Li; Pengzhi Hong; Chunxia Zhou; Shengli Sun; Zhongji Qian (Journal of Ocean University of China, 2023)

Decrease levels of bone morphogenetic protein 6 and noggin in chronic schizophrenia elderly - Lin Sun; Qi Qiu; Chunxia Ban; Sijia Fan; Shifu Xiao; Xia Li (Cognitive Neurodynamics, 2023)

Association of urinary iodine concentration with prediabetes/diabetes in adults: Analysis of the NHANES 2005–2016 - Jingmin Chen; Huanzhu Liang; Yuxuan Tan; Lin Wen; Ziang Guo; Jiyu Nie; Xiaoxiao Lin; Feng Huang; Jie Wang; Puyi Xing; Lihong Nie; Lihong Wang; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Association between co-exposure of polycyclic aromatic hydrocarbons and chronic obstructive pulmonary disease among the US adults: results from the 2013–2016 National Health and Nutrition Examination Survey - Lin Wen; Xiaosong Ben; Zhiyu Yang; Yingying Wu; Yuxuan Tan; Qian Chen; Huanzhu Liang; Yexin Li; Xiaomei Wu; Shan Liu; Xueqiong Weng; Dan Tian; et al. (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Coordination evaluation of urban tourism and urban development based on TOPSIS method—a case of Xiamen city - Chunxia Zheng; Yawei Wu; Yanqing Lin; Yawen Zheng (Environmental Science and Pollution Research, 2023)

Association between blood metal exposures and hyperuricemia in the U.S. general adult: A subgroup analysis from NHANES - Yuxuan Tan; Yingyin Fu; Feng Huang; Lin Wen; Xueqiong Weng; Huojie Yao; Huanzhu Liang; Mincong Kuang; Chunxia Jing (Chemosphere, 2023)

Tailoring the crumpled structures of a polyamide membrane with a heterostructural MXene-TiO2 interlayer for high water permeability - Jiawei Fu; Hang Xu; Tao Lin; Ao Wang; Anqi Wang; Chen Yao; Weihang Chen; Mingmei Ding; Chunxia Geng; Li Gao (Desalination, 2023)

Effects of desert riparian vegetation roots on the riverbank retreat process in the Tarim River in China - Quanli Zong; Tiegang Zheng; Ruize Tang; Kai Jin; Lin Li; Peng Qin; Chunxia Liu (Journal of Hydrology, 2023)

Multi-objective optimization of winter irrigation for cotton fields in salinized freeze-thaw areas - Ling Li; Hongguang Liu; Ping Gong; En Lin; Zhentao Bai; Pengfei Li; Chunxia Wang; Jing Li (European Journal of Agronomy, 2023)

Associations of single and multiple organophosphate pesticide exposure with female infertility in the USA: data from the 2015–2018 National Health and Nutrition Examination Survey - Yingying Wu; Xueqiong Weng; Shan Liu; Yuxuan Tan; Huanzhu Liang; Yexin Li; Lin Wen; Qian Chen; Chunxia Jing (Environmental Science and Pollution Research, 2022)

Relationship between urinary dichlorophenols and cognitive function among people over 60 years old from NHANES - Xueqiong Weng; Huanzhu Liang; Kun Liu; Jingmin Chen; Qiaoyuan Fei; Shan Liu; Xinrong Guo; Lin Wen; Yingying Wu; Zhiqiang Nie; Chunxia Jing (Environmental Science and Pollution Research, 2022)

Mixed effects of perfluoroalkyl and polyfluoroalkyl substances exposure on cognitive function among people over 60 years old from NHANES - Xueqiong Weng; Huanzhu Liang; Yuxuan Tan; Jingmin Chen; Qiaoyuan Fei; Shan Liu; Xinrong Guo; Lin Wen; Yingying Wu; Chunxia Jing (Environmental Science and Pollution Research, 2022)

Vertical and horizontal distributions of clinical antibiotic resistance genes and bacterial communities in Danjiangkou Reservoir, China - Chunxia Jiang; Xiong Pan; Hans-Peter Grossart; Li Lin; Jingya Shi; Yuyi Yang (Environmental Science and Pollution Research, 2021)

Performance of lab-scale microbial fuel cell coupled with unplanted constructed wetland for hexavalent chromium removal and electricity production - Chunxia Mu; Lin Wang; Li Wang (Environmental Science and Pollution Research, 2020)

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis - Daowen Wang; Sheng Li; Jiangang Jiang; Jiangtao Yan; Chunxia Zhao; Yan Wang; Yexin Ma; Hesong Zeng; Xiaomei Guo; Hong Wang; Jiarong Tang; Houjuan Zuo; et al. (Science China Life Sciences, 2019)

Novel Inhalable Ciprofloxacin Dry Powders for Bronchiectasis Therapy: Mannitol–Silk Fibroin Binary Microparticles with High-Payload and Improved Aerosolized Properties - Chunxia Liu; Ling Lin; Zhengwei Huang; Qiaoli Wu; Junhuang Jiang; Li Lv; Xiaoxia Yu; Guilan Quan; Guocheng Li; Chuanbin Wu (AAPS PharmSciTech, 2019)

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)

Phosphofructokinase-1 Negatively Regulates Neurogenesis from Neural Stem Cells - Fengyun Zhang; Xiaodan Qian; Cheng Qin; Yuhui Lin; Haiyin Wu; Lei Chang; Chunxia Luo; Dongya Zhu (Neuroscience Bulletin, 2016)

Distribution and phylogenetic analysis of Culex flavivirus in mosquitoes in China - Wenkai Liang; Xiaoxia He; Guifang Liu; Shaobai Zhang; Shihong Fu; Min Wang; Weixin Chen; Ying He; Xiaoyan Tao; Hongyue Jiang; Xiaojuan Lin; Xiaoyan Gao; et al. (Archives of Virology, 2015)

Pollution characteristics of the rivers in suburban Shanghai - Chunxia Yao; Zhenlou Chen; Shiyuan Xu; Ling Li; Li Wang; Shanshan Lin (Journal of Geographical Sciences, 2005)

Clinical and electrophysiological characterization of a novel mutation R863X in HERG C-terminus associated with long QT syndrome - Siyong Teng; Lijuan Ma; Yingxue Dong; Chunxia Lin; Jue Ye; Robert Bhring; Vitya Vardanyan; Yanzong Yang; Zhihu Lin; Olaf Pongs; Rutai Hui (Journal of Molecular Medicine, 2004)